Permanent neonatal diabetes: combining sulphonylureas with insulin may be an effective treatment - Misra,S; vedovato,N; cliff,E; de,franco E; hattersley,A; ashcroft,F; Oliver,N (Diabetic Medicine, 2018)
BackgroundPermanent neonatal diabetes caused by mutations in the KCNJ11 gene may be managed with highdose sulfonylureas. Complete transfer to sulfonylureas is not successful in all cases and can result in insulin monotherapy. In such cases, the outcomes of combining sulfonylureas with insulin have not been fully explored. We present the case of a woman with diabetes due to a KCNJ11 mutation, in whom combination therapy led to clinically meaningful improvements.CaseA 22yearold woman was found to have a KCNJ11 mutation (G334V) following diagnosis with diabetes at 3 weeks. She was treated with insulinpump therapy, had hypoglycaemia unawareness and suboptimal glycaemic control. We assessed the in vitro response of the mutant channel to tolbutamide in Xenopus oocytes and undertook sulfonylurea dosetitration with Cpeptide assessment and continuous glucose monitoring. In vitro studies predicted the G334V mutation would be sensitive to sulfonylurea therapy [91 ± 2% block (n = 6) with 0.5 mM tolbutamide]. Cpeptide increased following a glibenclamide test dose (from 5 to 410 pmol/l). Glibenclamide dosetitration was undertaken: a lower glibenclamide dose did not reduce blood glucose levels, but at 1.2 mg/kg/day insulin delivery was reduced to 0.1 units/h. However, when insulin was stopped, hyperglycaemia ensued. Glibenclamide was further increased (2 mg/kg/day), but oncedaily longacting insulin was still required to maintain glycaemia. This resulted in improved HbA1c of 52 mmol/mol (6.9%), restoration of hypoglycaemia awareness and reduced glycaemic variability.ConclusionIn people with KCNJ11 mutations causing permanent neonatal diabetes, and where complete transfer is not possible, consideration should be given to dual insulin and sulfonylurea therapy.